2007
DOI: 10.2167/ijm042.0
|View full text |Cite
|
Sign up to set email alerts
|

Is L3 Phonological Competence Affected by the Learner's Level of Bilingualism?

Abstract: Research on the effect of bilingualism on third language acquisition was initially set in the framework of the study of potential differences between monolinguals acquiring a second language and bilinguals learning a third language. However, many authors have already started to concentrate on third language acquisition itself, and have investigated if there are any differences with regard to target language competence as a function of certain characteristics of the bilingual learner. The number of specific stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Moreover, it has been suggested that bilinguals surpass monolinguals in the completion of specific cognitive tasks, for example in their ability to resolve conflicting information by inhibiting the misleading source (Bialystok, 2012: 425). A similar conclusion was reached by Gallardo del Puerto (2007) in relation to Cummins' (1984) CALP (cognitive academic learning proficiency) and BICS (basic interpersonal communication skills) distinction. He suggests that a bilingual advantage would be more apparent in linguistic areas that depend on cognitive development (CALP) but not necessarily in areas that are less related to cognitive maturation (BICS), such as pronunciation.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Moreover, it has been suggested that bilinguals surpass monolinguals in the completion of specific cognitive tasks, for example in their ability to resolve conflicting information by inhibiting the misleading source (Bialystok, 2012: 425). A similar conclusion was reached by Gallardo del Puerto (2007) in relation to Cummins' (1984) CALP (cognitive academic learning proficiency) and BICS (basic interpersonal communication skills) distinction. He suggests that a bilingual advantage would be more apparent in linguistic areas that depend on cognitive development (CALP) but not necessarily in areas that are less related to cognitive maturation (BICS), such as pronunciation.…”
supporting
confidence: 63%
“…This was confirmed for general multilingual linguistic experience by Enomoto (1994) and Beach (2001) for perceptual performance in L3 Japanese and L3 Thai, and for specific linguistic experience in an ERP experiment by Tremblay (2010). Evidence to the contrary was found by González Ardeo (2001) and Gallardo del Puerto (2007).…”
mentioning
confidence: 84%
“…Similarly, school-age French-English bilingual and English monolingual children showed no difference in discriminating non-native Russian phonemes (Lambert and MacNamara 1969) even though this same task was used in Rabinovitch and Parver (1966) and their results showed that bilingual university students performed better than monolingual university students. Gallardo del Puerto (2007) showed that the degree of bilingualism (high vs. low use of both languages) does not affect non-native phoneme discrimination, and the author concludes that bilingualism does not affect non-native phonetic discrimination even though there was no comparison to monolingual data.…”
Section: Visual Inspection Of the Vowels Plotted Inmentioning
confidence: 97%
“…For example, research examining the linguistic knowledge of heritage speakers in relation to late L2 learners is helping to inform language course design so as to better serve the unique needs of heritage language learners. Studies of third language (L3) learners are investigating what factors influence speech learning in multilingual situations (Gallardo del Puerto, 2007), how L3 learning resembles and differs from L2 learning (Onishi, 2013;Wrembel, 2014), and how L3 learning may influence the phonological representations and processes associated with previously learned languages (Cabrelli Amaro, 2017), in line with the multicompetence view of language development over the lifespan (Cook, 1991(Cook, , 1992(Cook, , 2003. Finally, it would be remiss not to mention the work of scholars who are connecting L2 speech research to L2 instructional practices and strategies (see, e.g., Mora and Levkina, 2017).…”
Section: Discussionmentioning
confidence: 99%